Maternal and fetal outcomes in overweight and obese pregnant women - Shetty, Isha; Nandan, Neetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The prevalence of obesity among child bearing age women is rising in India and it has adverse implications on mother and fetus. The aim of this study is to assess impact of overweight and obese mothers on antenatal, intrapartum, postpartum and neonatal outcomes. Methods: It is an observational hospital-based study. Pregnant women were categorized into three groups depending on their body mass index (BMI)–normal (BMI–18.5–24.9 kg/m2), overweight (BMI–25.0–29.9 kg/m2) or obese (BMI>40 kg/m2). Antepartum, intrapartum, postpartum and neonatal complications were noted. Results: Out of 104 women, 36 each were in normal and overweight group and 32 were in obese group. Obese and overweight women had higher rate of caesarean section (68.8% and 44.4%) compared to normal group (30.6%, P-value – 0.006). Failed induction rate was more in obese and overweight women (12.5% and 11.1%) compared to normal group (2.8%) but not statistically significant. Postpartum hemorrhage (PPH) was high in normal group (36.1%, P-value–0.040). Neonatal hyperbilirubinemia requiring NICU admission was significantly high in overweight and normal group (P-value–0.000). Gestational diabetes and hypertension were comparatively more in obese and overweight group but not statistically significant. Conclusions: Women who are obese and overweight pregnant women have increased risk for caesarean section and have higher rate of failed induction. They have higher tendency to develop gestational diabetes and hypertension in pregnancy. Postpartum hemorrhage was high in normal BMI women. Neonatal intensive care admissions for neonatal hyperbilirubinemia were high in overweight and normal BMI women.